Expression of Foreign Genes Demonstrates the Effectiveness of Pollen-Mediated Transformation in Zea mays - Yang, Liyan; Cui, Guimei; Wang, Yixue; Hao, Yaoshan; Du, Jianzhong; Zhang, Hongmei; Wang, Changbiao; Zhang, Huanhuan; Wu, Shu-Biao; Sun, Yi (Frontiers in Plant Science, 2017)
Plant genetic transformation has arguably been the core of plant improvement in recent decades. Efforts have been made to develop in planta transformation systems due to the limitations present in the tissue-culture-based methods. Herein, we report an improved in planta transformation system, and provide the evidence of reporter gene expression in pollen tube, embryos and stable transgenicity of the plants following pollen-mediated plant transformation with optimized sonication treatment of pollen. The results showed that the aeration at 4C treatment of pollen grains in sucrose prior to sonication significantly improved the pollen viability leading to improved kernel set and transformation efficiency. SEM observation revealed that the removal of operculum covering pollen pore by ultrasonication might be one of the reasons for the pollen grains to become competent for transformation. Evidences have shown that the eGfp gene was expressed in the pollen tube and embryos, and the Cry1Ac gene was detected in the subsequent T1 and T2 progenies, suggesting the successful transfer of the foreign genes to the recipient plants. The southern blot analysis of Cry1Ac gene in T2 progenies and PCR-identified Apr gene segregation in T2 seedlings confirmed the stable inheritance of the transgene. The outcome illustrated that the pollen-mediated genetic transformation system can be widely applied in the plant improvement programs with apparent advantages over tissue-culture-based transformation methods.